Associations among personality traits, emotional states, and self-management behaviors with quality of life in type 2 diabetes: a structural equation modeling approach examining emotional mediation - Fu, Wen; Xu, Jue; Jiang, Caixia; Liu, Shijun; Yang, Cheng; Qiu, Xin (Frontiers in Psychology, 2025)
BackgroundCurrent empirical literature demonstrates a paucity of evidence elucidating the intricate network relationships among personality traits, emotion states, self-management behaviors, and quality of life (QOL) in patients with type 2 diabetes mellitus (T2DM). This cross-sectional study aimed to investigate these relationships using structural equation modeling (SEM).MethodsA cohort of 839 T2DM patients was systematically recruited from 69 community health service centers in Hangzhou, China, between 2016 and 2020. Standardized instruments were administered to assess demographic characteristics, personality traits (Chinese Big Five Personality Inventory-15, CBF-PI-15), emotional states (Self-Rating Anxiety Scale [SAS] and Self-Rating Depression Scale [SDS]), self-management behaviors (Type 2 Diabetes Self-Care Scale, 2-DSCS), and QOL (MOS 36-Item Short-Form Health Survey, SF-36). Data analyses were performed using SPSS 26.0 and AMOS 21.0.ResultsDescriptive statistics revealed the highest mean score for agreeableness (13.58 ± 2.55), whereas self-management subdomains exhibited comparatively lower scores (blood glucose monitoring: 12.17 ± 4.10; regular exercise: 12.35 ± 4.89). Significant anxiety and depressive symptoms were present in 20.4 and 28.6% of participants, respectively. Bivariate correlations showed significant positive associations between self-management behaviors and both psychological/physiological QOL dimensions, alongside negative correlations with anxiety, depression, and neuroticism. The SEM analysis yielded excellent model fit indices (χ2/df = 3.556, AGFI = 0.946, GFI = 0.967, CFI = 0.957, IFI = 0.957, RMSEA = 0.055), with anxiety emerging as the most robust predictor of QOL (β = −0.542), followed by depression (β = −0.360) and self-management behaviors (β = 0.342). Mediation analysis confirmed the significant intermediary roles of anxiety and depression in pathway linking self-management behaviors to QOL (indirect effects accounting for 33.70%, 30.33% of total variance).ConclusionThese findings elucidate the complex psychobehavioral mechanisms underlying QOL in T2DM patients, highlighting the critical mediating role of emotional states between self-management and QOL. The results underscore the imperative for integrated interventions targeting both emotional regulation and behavioral modification in diabetes care protocols.